A novel approach to evaluate mixed-mode SIFs for a through-thickness crack in a welding residual stress field using an effective welding simulation method. (15th June 2018) - Gadallah, Ramy; Osawa, Naoki; Tanaka, Satoyuki; Tsutsumi, Seiichiro
Highlights: Interaction integral method available in WARP3D code was modified. Normal and shear stress components are included in mixed-mode SIF solutions. Efficient in-house welding simulation code was adopted to predict residual stress. Influence of welding residual stress was considered in mixed-mode SIF solutions. Influence of crack angle and weld orientation on mixed-mode SIFs was discussed. Abstract: This paper accurately evaluates mixed-mode SIFs (MM-SIFs) for cracks in welding residual stress (WRS) fields using a novel approach based on finite element method (FEM). For this reason, the interaction integral method (IIM) available in WARP3D, an open source code, was developed to include normal and shear stress components in MM-SIF solutions. The effectiveness of the developed WARP3D-IIM was verified based on the superposition method and by means of well-established analytical and numerical reference solutions using an inclined through-thickness cracked FE model. After validating the adequacy of the developed WARP3D-IIM, different welding simulations were conducted using JWRIAN (Joining and Welding Research Institute ANalysis). JWRIAN, a sophisticated welding simulation in-house code, was adopted as a welding simulation tool to predict WRS. Different weld line (WL) orientations, as well as different perpendicular distances between WLs, were performed to investigate their influence on the behavior of MM-SIFs. The developed WARP3D-IIM and superposition method were thereafter employed to evaluate MM-SIF solutions for an inclined through-thickness crack in the simulated WRS fields. Different crack angles were also employed to examine the effect of the induced WRS on calculated MM-SIFs. SIF solutions resulting from WRS were validated with analytical reference solutions. Results showed that WRS has a considerable influence on the behavior of MM-SIFs. Moreover, WL orientation as well as the perpendicular distance between WLs revealed a significant influence on the induced WRS and thus MM-SIF solutions. On the other hand, the crack angle showed a remarkable effect on the behavior of MM-SIFs. MM-SIFs calculated at through-thickness crack fronts were influenced by the induced WRS distribution as well as crack angle.